Evaluation of the status of marine fishery resources of Tamil Nadu, India using surplus production models (Indian Journal of Geo-Marine Sciences (IJMS), 2024)
The present study used surplus production models for the assessment of fisheries stock and to evaluate the marine fishery status of Tamil Nadu. Present study computed and analysed annual catch and effort between 1998 and 2018 using Catch Effort Data Analysis (CEDA) software. The mean annual catch of Tamil Nadu marine fisheries was 4.14 lakh tonnes, ranging from 2.87 lakh tonnes (2005) to 5.20 lakh tonnes (2018). The Biological Reference Points (BRP), such as Maximum Sustainable Yield (MSY), Biomass at MSY (BMSY), and Fishing mortality at MSY (FMSY), were estimated using three error assumptions (Normal, Log Normal and Gamma) of Fox, Schaefer, and Pella-Tomlinson production models for Initial Proportion (IP) ranging from 0.1 to 1. From the results, MSY, BMSY and FMSY estimated by the best fit Schaefer-Log Normal (IP value of 0.8) were 5.32 lakh tonnes, 35.3 million tonnes and 0.151, respectively. The BRP determined from the Schaefer and Pella-Tomlinson models was similar. The predicted MSY values were higher than the most recent catch (5.20 lakh tonnes) of 2018. According to the reference point results, the stocks are secure; however, it is advised to keep fishing at present level in order to preserve the stock at a nearly optimal fishing pressure.